Incidence of Thyroid Carcinoma in Patients Undergoing Thyroidectomy for Nodular Goiter in Bitlis Province (Annals of Medical Research, 2021)
None
Keywords: Endemic Nodular Goiter; Thyroidectomy; Thyroid Carcinoma